Financial performance of China companies listed on Singapore Exchange. - Fong, Jilliana Yan Harn. (2008)
This study examines the financial performance of China companies listed on the Singapore Stock Exchange (SGX) in 2005. The objective is to investigate the differences in performance between China listings and the overall stock market. In the study we compare the differences in averages of key financial indicators such as Return on Equity (ROE), Return on Assets (ROA), Earnings per Share (EPS), Price-Earnings Ratio (P/E) and Net Asset Value per Share (NAVPS) to determine whether there is a noticeable distinction between the two groups under study. Besides, we also examined how the financials of recently-listed China companies differ from those which have been listed for a longer period of time. Further, a more in depth analysis of ROE was performed by looking at the individual components that form the Du-Pont equation. Our findings contributed to the understanding to the financial behaviour of Singapore-listed China companies against all companies listed on the SGX as a whole.